A method for the preparation of an anionically polymerized SIS elastomer

CN122940960APending Publication Date: 2026-10-20NINGBO JINHAI CHENGUANG CHEM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611067036.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0007]本发明所要解决的技术问题是针对现有技术的现状,提供一种阴离子聚合合成高熔体流动速率、透明SIS弹性体的制备方法,以解决现有技术中残留极性杂质和金属离子会影响SIS产品颜色和热稳定性的问题

Benefits of technology

[0025]与现有技术相比,本发明的优点在于:本发明采用特定化合物水溶液与SIS胶液混合后静置分离,可有效脱除胶液中的金属离子与微量极性杂质,过程中无需添加其他助剂;所得胶液送入干法脱挥系统处理,不仅从源头上消除了金属离子与极性杂质对产品颜色和热稳定性的影响,且不会引发设备腐蚀,最终可制得无色透明、热稳定性与流动性优异的SIS弹性体,能够满足高端热熔胶、透明改性塑料、食品医疗级弹性体等领域的应用需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

A method for preparing SIS elastomers by anionic polymerization includes the following steps: Step 1, adding styrene monomers, cyclohexane solvent, and tetrahydrofuran activator to a reactor, adding n-butyllithium initiator, and reacting under stirring; Step 2, adding isoprene monomer, and controlling the reaction temperature; Step 3, adding styrene monomers, and continuing the reaction under stirring; Step 4, adding a terminator, and continuing the reaction under stirring to obtain a gel; Step 5, adding an aqueous solution containing a specific compound to the gel, allowing it to react with metal ions in the gel to generate a precipitate that is soluble in water but insoluble in the gel, while simultaneously washing away trace amounts of water-soluble polar impurities, and allowing it to stand for separation; Step 6, concentrating by flash evaporation; Step 7, dry devolatilization, followed by extrusion molding and drying to obtain the SIS elastomer product. This invention solves the problem of residual polar impurities and metal ions affecting the color and thermal stability of SIS products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer material synthesis technology, specifically relating to a method for preparing SIS elastomers by anionic polymerization. Background Technology

[0002] Styrene-isoprene-styrene block copolymer (SIS) has become a widely used polymer material in adhesives, plastics modification and other fields due to its excellent viscoelastic balance, good compatibility with tackifying resins, and outstanding high initial tack and fast tack properties.

[0003] Currently, the domestic production of SIS generally adopts the wet devolatilization process of steam and hot water condensation. This process uses a large amount of hot water, which can effectively remove most of the metal ions and polar impurities in the adhesive solution. Moreover, the devolatilization temperature is below 100℃, and the product quality is relatively easy to control. However, the adhesive block after devolatilization is prone to clogging the pump body, adhering to the equipment wall and filter screen, and is also prone to adhering to the chain plate during the drying stage. The production has high energy consumption, short operating cycle, and the produced products have defects such as poor fluidity and opacity, which cannot meet the demand for high fluidity and high transparency SIS elastomer materials.

[0004] Compared to wet devolatilization, dry devolatilization uses flash evaporation combined with twin-screw extrusion for devolatilization, eliminating problems such as pump clogging, adhesion to equipment walls, filters, and conveyor belts. It can produce SIS thermoplastic elastomers with good flowability and transparency, and the process is shorter and has lower energy consumption. However, the devolatilization temperature in dry devolatilization is close to 200℃, requiring high levels of impurities in the product, especially metal ions, chloride ions, and polar impurities. Otherwise, it can lead to a series of problems such as product discoloration, decreased thermal stability, and equipment corrosion. Therefore, existing technologies mostly use wet devolatilization processes, which cannot meet the requirements for high-flowability, high-transparency SIS elastomer materials.

[0005] Chinese invention patent application number 201610772604.7 and authorization announcement number CN106220798B discloses a high melt index, high transparency SIS elastomer and its preparation method. It utilizes alkyl lithium as a catalyst, reacting styrene and isoprene as raw materials to prepare a SIS adhesive. The SIS elastomer is then prepared through steps such as blending, flash evaporation concentration, dry devolatilization, extrusion, molding, and drying. However, the SIS products produced using this method still easily retain trace amounts of polar impurities and metal ions, leading to inconsistencies in color and thermal stability.

[0006] Chinese invention patent application No. 202111059809.8 and publication No. CN115785306A discloses an industrial-scale continuous method for removing metal ions from SEBS / SEPS / SBS / SIS adhesive solutions. The method involves mixing carboxylic acid with the SEBS / SEPS / SBS / SIS adhesive solution, performing a first emulsification shearing process to convert metal ions into carboxylate salts, adding water, and then performing a second emulsification shearing process to dissolve the carboxylate salts into the aqueous phase. Finally, the saline phase is removed using an electro-dehydration device, achieving metal ion separation. This method is cumbersome, requiring not only a complex electro-dehydration device but also the introduction of a demulsifier. Furthermore, chlorine-containing demulsifiers can easily corrode the equipment. Additionally, the method does not specify the subsequent devolatilization process for the adhesive solution. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide a method for preparing a transparent SIS elastomer with high melt flow rate by anionic polymerization, in order to solve the problem that residual polar impurities and metal ions in the prior art affect the color and thermal stability of SIS products.

[0008] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: a method for preparing anionic polymerized SIS elastomers, characterized by comprising the following steps:

[0009] Step 1: Add styrene monomers, solvent cyclohexane and activator tetrahydrofuran to the reactor, mix well and heat to 45℃~55℃, add initiator n-butyllithium, and react under stirring for 20min~30min.

[0010] Step 2: Add isoprene monomer at a temperature of 55℃~60℃, control the reaction temperature below 105℃, and react for 20min~30min.

[0011] Step 3: Add styrene monomers and continue the reaction for 20 to 30 minutes with stirring.

[0012] Step 4: Add the terminator and continue the reaction for 5 to 10 minutes while stirring to obtain the adhesive solution;

[0013] Step 5: Add the aqueous solution containing the specific compound to the adhesive solution to react with the metal ions in the adhesive solution to generate a precipitate that is soluble in water but insoluble in the adhesive solution. At the same time, wash away the trace amounts of polar impurities that are soluble in water and allow the mixture to stand and separate.

[0014] Step 6: Flash evaporate the adhesive solution after step 5 to concentrate it.

[0015] Step 7: The concentrated adhesive solution obtained in Step 6 is subjected to dry devolatilization, followed by extrusion, molding, and drying to obtain the SIS elastomer product.

[0016] Preferably, the mass ratio of the total amount of styrene monomers to the total amount of isoprene monomers is 1:9 to 1:1.

[0017] Preferably, the styrene monomer is styrene or α-methylstyrene.

[0018] Preferably, the concentration of the aqueous solution of the specific compound is 0.1 wt% to 10.0 wt%.

[0019] Preferably, the specific compound is citric acid, stearic acid, hydroxysulfonic acid, ammonia, or NaHCO3.

[0020] Preferably, the terminating agent is water, an alcohol, an acid, or a hindered phenol.

[0021] Preferably, in step 4, antioxidant 1076 and antioxidant 168 are added to the adhesive solution, and the amount of antioxidant 1076 and antioxidant 168 is 0.3wt% to 0.6wt% of the total amount of styrene monomers.

[0022] Furthermore, in step 4, the solid content of the adhesive solution is 12wt% to 18wt%.

[0023] In the above embodiments, preferably, the melt index of the SIS elastomer product is 2.0 g / 10 min to 200.0 g / 10 min.

[0024] Preferably, the molecular weight of the SIS elastomer product is 50,000 to 300,000.

[0025] Compared with the prior art, the advantages of this invention are as follows: This invention uses a specific compound aqueous solution to mix with SIS adhesive and then allows it to stand for separation, which can effectively remove metal ions and trace amounts of polar impurities from the adhesive without the need to add other additives. The resulting adhesive is then sent to a dry devolatilization system for treatment, which not only eliminates the influence of metal ions and polar impurities on the product's color and thermal stability from the source, but also does not cause equipment corrosion. In the end, a colorless and transparent SIS elastomer with excellent thermal stability and flowability can be obtained, which can meet the application needs of high-end hot melt adhesives, transparent modified plastics, food and medical grade elastomers and other fields.

[0026] This invention first mixes a specific compound aqueous solution with a SIS emulsion and then allows it to stand for separation. Then, it performs a dry devolatilization process. Without introducing other additives, it can effectively remove metal ions and trace amounts of polar impurities from the emulsion. At the higher devolatilization temperature of the dry devolatilization process, it will not cause problems such as product discoloration, decreased thermal stability, or equipment corrosion. Finally, a colorless and transparent SIS elastomer with excellent thermal stability and flowability is obtained. Detailed Implementation

[0027] Example 1:

[0028] A method for preparing SIS elastomers by anionic polymerization, comprising the following steps:

[0029] Step 1: In a 5L reactor, add 2.5kg of measured cyclohexane, 40g of styrene, and 0.3g of tetrahydrofuran. Add 4.5mmol of initiator n-butyllithium at 45-55℃ and react for 25 minutes. Then add 420g of measured isoprene, controlling the maximum temperature below 105℃, and react for 25 minutes. Next, add 40g of styrene and react for 25 minutes. Finally, add 0.3g of ethanol and react for 10 minutes. Discharge the product, add 2.0g of antioxidant 1076 and 2.5g of antioxidant 168, and stir until homogeneous.

[0030] Step 2: Stir the adhesive solution obtained in Step 1 with 10g of 5.0wt% stearic acid aqueous solution for 30min, and let it stand to separate into layers;

[0031] Step 3: The adhesive solution treated in Step 2 is concentrated by flash evaporation at 160℃ to a solid content of 50wt%;

[0032] Step 4: The concentrated adhesive solution from step 3 is fed into a devolatilizer with four devolatilization ports. Under a vacuum of -90 kPa, the solvent evaporates from the devolatilization ports. The molten product extruded from the die head template of the devolatilizer through pressure difference is cut into elliptical particles of about 2 mm in length by a high-speed rotating cutter closely attached to the template. The particles are carried into a centrifugal dryer by the circulating water in the underwater pelletizing system. After the particles are spun dry in the centrifugal dryer, granular products are obtained, and SIS elastomer products are prepared.

[0033] Example 2:

[0034] A method for preparing SIS elastomers by anionic polymerization, comprising the following steps:

[0035] Step 1: In a 5L reactor, add 2.5kg of measured cyclohexane, 40g of styrene, and 0.3g of tetrahydrofuran. Add 5.0mmol of initiator n-butyllithium at 45-55℃ and react for 25 minutes. Then add 420g of measured isoprene, controlling the maximum temperature below 105℃, and react for 25 minutes. Next, add 40g of styrene and react for 25 minutes. Finally, add 0.3g of ethanol and react for 10 minutes. Discharge the product, add 2.0g of antioxidant 1076 and 2.5g of antioxidant 168, and stir until homogeneous.

[0036] Step 2: Stir the adhesive solution obtained in Step 1 with 100g of 5.0wt% stearic acid aqueous solution for 30 minutes, and let it stand to separate into layers;

[0037] Step 3: The adhesive solution treated in Step 2 is concentrated by flash evaporation at 160℃ to a solid content of 50 wt%.

[0038] Step 4: The concentrated adhesive solution from step 3 is fed into a devolatilizer with four devolatilization ports. Under a vacuum of -90 kPa, the solvent evaporates from the devolatilization ports. The molten product extruded from the die head template of the devolatilizer through pressure difference is cut into elliptical particles of about 2 mm in length by a high-speed rotating cutter closely attached to the template. The particles are carried into a centrifugal dryer by the circulating water in the underwater pelletizing system. After the particles are spun dry in the centrifugal dryer, granular products are obtained, and SIS elastomer products are prepared.

[0039] Example 3:

[0040] A method for preparing SIS elastomers by anionic polymerization, comprising the following steps:

[0041] Step 1: In a 5L reactor, add 2.5kg of measured cyclohexane, 40g of styrene, and 0.3g of tetrahydrofuran. Add 5.5mmol of initiator n-butyllithium at 45-55℃ and react for 25 minutes. Then add 420g of measured isoprene, controlling the maximum temperature below 105℃, and react for 25 minutes. Next, add 40g of styrene and react for 25 minutes. Finally, add 0.3g of ethanol and react for 10 minutes. Discharge the product, add 2.0g of antioxidant 1076 and 2.5g of antioxidant 168, and stir until homogeneous.

[0042] Step 2: Stir the adhesive solution obtained in Step 1 with 500g of 5.0wt% stearic acid aqueous solution for 30 minutes, and let it stand to separate into layers;

[0043] Step 3: The adhesive solution treated in Step 2 is concentrated by flash evaporation at 160℃ to a solid content of 50 wt%.

[0044] Step 4: The concentrated adhesive solution from step 3 is fed into a devolatilizer with four devolatilization ports. Under a vacuum of -90 kPa, the solvent evaporates from the devolatilization ports. The molten product extruded from the die head template of the devolatilizer through pressure difference is cut into elliptical particles of about 2 mm in length by a high-speed rotating cutter closely attached to the template. The particles are carried into a centrifugal dryer by the circulating water in the underwater pelletizing system. After the particles are spun dry in the centrifugal dryer, granular products are obtained, and SIS elastomer products are prepared.

[0045] Example 4:

[0046] A method for preparing SIS elastomers by anionic polymerization, comprising the following steps:

[0047] Step 1: In a 5L reactor, add 2.5kg of measured cyclohexane, 40g of styrene, and 0.3g of tetrahydrofuran. Add 6.5mmol of initiator n-butyllithium at 45-55℃ and react for 25 minutes. Then add 420g of measured isoprene, controlling the maximum temperature below 105℃, and react for 25 minutes. Next, add 40g of styrene and react for 25 minutes. Finally, add 0.3g of ethanol and react for 10 minutes. Discharge the product, add 2.0g of antioxidant 1076 and 2.5g of antioxidant 168, and stir until homogeneous.

[0048] Step 2: Stir the adhesive solution obtained in Step 1 with 1000g of 5.0wt% stearic acid aqueous solution for 30min, and let it stand to separate into layers;

[0049] Step 3: The adhesive solution treated in Step 2 is concentrated by flash evaporation at 160℃ to a solid content of 50 wt%.

[0050] Step 4: The concentrated adhesive solution from step 3 is fed into a devolatilizer with four devolatilization ports. Under a vacuum of -90 kPa, the solvent evaporates from the devolatilization ports. The molten product extruded from the die head template of the devolatilizer through pressure difference is cut into elliptical particles of about 2 mm in length by a high-speed rotating cutter closely attached to the template. The particles are carried into a centrifugal dryer by the circulating water in the underwater pelletizing system. After the particles are spun dry in the centrifugal dryer, granular products are obtained, and SIS elastomer products are prepared.

[0051] Example 5:

[0052] A method for preparing SIS elastomers by anionic polymerization, comprising the following steps:

[0053] Step 1: In a 5L reactor, add 2.5kg of measured cyclohexane, 40g of styrene, and 0.3g of tetrahydrofuran. Add 5.0mmol of initiator n-butyllithium at 45-55℃ and react for 25 minutes. Then add 420g of measured isoprene, controlling the maximum temperature below 105℃, and react for 25 minutes. Next, add 40g of styrene and react for 25 minutes. Finally, add 0.3g of ethanol and react for 10 minutes. Discharge the product, add 2.0g of antioxidant 1076 and 2.5g of antioxidant 168, and stir until homogeneous.

[0054] Step 2: Stir the adhesive solution obtained in Step 1 with 100g of 5.0wt% citric acid aqueous solution for 30 minutes, and let it stand to separate into layers;

[0055] Step 3: The adhesive solution treated in Step 2 is concentrated by flash evaporation at 160℃ to a solid content of 50 wt%.

[0056] Step 4: The concentrated adhesive solution from step 3 is fed into a devolatilizer with four devolatilization ports. Under a vacuum of -90 kPa, the solvent evaporates from the devolatilization ports. The molten product extruded from the die head template of the devolatilizer through pressure difference is cut into elliptical particles of about 2 mm in length by a high-speed rotating cutter closely attached to the template. The particles are carried into a centrifugal dryer by the circulating water in the underwater pelletizing system. After the particles are spun dry in the centrifugal dryer, granular products are obtained, and SIS elastomer products are prepared.

[0057] Example 6:

[0058] A method for preparing SIS elastomers by anionic polymerization, comprising the following steps:

[0059] Step 1: In a 5L reactor, add 2.5kg of measured cyclohexane, 40g of styrene, and 0.3g of tetrahydrofuran. Add 5.0mmol of initiator n-butyllithium at 45-55℃ and react for 25 minutes. Then add 420g of measured isoprene, controlling the maximum temperature below 105℃, and react for 25 minutes. Next, add 40g of styrene and react for 25 minutes. Finally, add 0.3g of ethanol and react for 10 minutes. Discharge the product, add 2.0g of antioxidant 1076 and 2.5g of antioxidant 168, and stir until homogeneous.

[0060] Step 2: Stir the adhesive solution obtained in Step 1 with 100g of 5.0wt% NaHCO3 aqueous solution for 30min, and let it stand to separate into layers;

[0061] Step 3: The adhesive solution treated in Step 2 is concentrated by flash evaporation at 160℃ to a solid content of 50 wt%.

[0062] Step 4: The concentrated adhesive solution from step 3 is fed into a devolatilizer with four devolatilization ports. Under a vacuum of -90 kPa, the solvent evaporates from the devolatilization ports. The molten product extruded from the die head template of the devolatilizer through pressure difference is cut into elliptical particles of about 2 mm in length by a high-speed rotating cutter closely attached to the template. The particles are carried into a centrifugal dryer by the circulating water in the underwater pelletizing system. After the particles are spun dry in the centrifugal dryer, granular products are obtained, and SIS elastomer products are prepared.

[0063] Comparative Example 1:

[0064] A method for preparing SIS elastomers by anionic polymerization, comprising the following steps:

[0065] Step 1: In a 5L reactor, add 2.5kg of measured cyclohexane, 40g of styrene, and 0.3g of tetrahydrofuran. Add 4.5mmol of initiator n-butyllithium at 45-55℃ and react for 25 minutes. Then add 420g of measured isoprene, controlling the maximum temperature below 105℃, and react for 25 minutes. Next, add 40g of styrene and react for 25 minutes. Finally, add 0.3g of ethanol and react for 10 minutes. Discharge the product, add 2.0g of antioxidant 1076 and 2.5g of antioxidant 168, and stir until homogeneous.

[0066] Step 2: The adhesive solution obtained in Step 1 is concentrated by flash evaporation at 160℃ to a solid content of 50wt%;

[0067] Step 3: The concentrated adhesive solution from step 2 is fed into a devolatilizer with four devolatilization ports. Under a vacuum of -90 kPa, the solvent evaporates from the devolatilization ports. The molten product extruded from the die head template of the devolatilizer through pressure difference is cut into elliptical particles of about 2 mm in length by a high-speed rotating cutter closely attached to the template. The particles are carried into a centrifugal dryer by the circulating water in the underwater pelletizing system. After the particles are spun dry in the centrifugal dryer, granular products are obtained, and SIS elastomer products are prepared.

[0068] Comparative Example 2:

[0069] A method for preparing SIS elastomers by anionic polymerization, comprising the following steps:

[0070] Step 1: In a 5L reactor, add 2.5kg of measured cyclohexane, 40g of styrene, and 0.3g of tetrahydrofuran. Add 6.5mmol of n-butyllithium initiator at 45-55℃ and react for 25 minutes. Then add 420g of measured isoprene, controlling the maximum temperature below 105℃, and react for 25 minutes. Next, add 40g of styrene and react for 25 minutes. Finally, add 0.3g of ethanol and react for 10 minutes. Discharge the product, add 2.0g of antioxidant 1076 and 2.5g of antioxidant 168, and stir until homogeneous.

[0071] Step 2: The adhesive solution from Step 1 is concentrated by flash evaporation at 160℃ to a solid content of 50wt%;

[0072] Step 3: The concentrated adhesive solution from step 2 is fed into a devolatilizer with four devolatilization ports. Under a vacuum of -90 kPa, the solvent evaporates from the devolatilization ports. The molten product extruded from the die head template of the devolatilizer through pressure difference is cut into elliptical particles of about 2 mm in length by a high-speed rotating cutter closely attached to the template. The particles are carried into a centrifugal dryer by the circulating water in the underwater pelletizing system. After the particles are spun dry in the centrifugal dryer, granular products are obtained, thus preparing the SIS elastomer product.

[0073] The molecular weight, melt index, transparency, yellow index, and aging yellow index of the SIS elastomer products obtained in the above embodiments and comparative examples are shown in Table 1 below:

[0074] Table 1:

[0075]

[0076] As shown in Table 1, the melt index of the SIS elastomer prepared using the method of this invention is 11-140 g / 10 min, and it exhibits good transparency. Furthermore, water washing significantly improves the yellow index and aging performance of the product. When the amount of stearic acid is 1% of the total monomer content, the water washing effect is essentially saturated. The water washing effects of acidic substances citric acid and stearic acid, and alkaline substances NaHCO3 are basically equivalent.

Claims

1. A method for preparing anionic polymerized SIS elastomer, characterized in that... Includes the following steps: Step 1: Add styrene monomers, solvent cyclohexane and activator tetrahydrofuran to the reactor, mix well and heat to 45℃~55℃, add initiator n-butyllithium, and react under stirring for 20min~30min. Step 2: Add isoprene monomer at a temperature of 55℃~60℃, control the reaction temperature below 105℃, and react for 20min~30min. Step 3: Add styrene monomers and continue the reaction for 20 to 30 minutes with stirring. Step 4: Add the terminator and continue the reaction for 5 to 10 minutes while stirring to obtain the adhesive solution; Step 5: Add the aqueous solution containing the specific compound to the adhesive solution to react with the metal ions in the adhesive solution to generate a precipitate that is soluble in water but insoluble in the adhesive solution. At the same time, wash away the trace amounts of polar impurities that are soluble in water and allow the mixture to stand and separate. Step 6: Flash evaporate the adhesive solution after step 5 to concentrate it. Step 7: The concentrated adhesive solution obtained in Step 6 is subjected to dry devolatilization, followed by extrusion, molding, and drying to obtain the SIS elastomer product.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the total amount of styrene monomers to the total amount of isoprene monomers is 1:9 to 1:

1.

3. The preparation method according to claim 1, characterized in that: The styrene monomer is styrene or α-methylstyrene.

4. The preparation method according to claim 1, characterized in that: The concentration of the aqueous solution of the specific compound is 0.1 wt% to 10.0 wt%.

5. The preparation method according to claim 1, characterized in that: The specific compound is citric acid, stearic acid, hydroxysulfonic acid, ammonia, or NaHCO3.

6. The preparation method according to claim 1, characterized in that: The terminating agent is water, alcohol, acid, or hindered phenol.

7. The preparation method according to claim 1, characterized in that: In step 4, antioxidant 1076 and antioxidant 168 are added to the adhesive solution. The amount of antioxidant 1076 and antioxidant 168 is 0.3wt% to 0.6wt% of the total amount of styrene monomers.

8. The preparation method according to claim 1, characterized in that: In step 4, the solid content of the adhesive solution is 12wt% to 18wt%.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The melt index of the SIS elastomer product is 2.0 g / 10 min to 200.0 g / 10 min.

10. The preparation method according to any one of claims 1 to 8, characterized in that: The molecular weight of the SIS elastomer product is 50,000 to 300,000.

Citation Information

Patent Citations

  • A high melt index, high transparency SIS elastomer and its preparation method

    CN106220798B

  • Method for industrially and continuously removing metal ions in SEBS / SEPS / SBS / SIS glue solution

    CN115785306A